Associations of adaptive immune cell subsets with measles, mumps, and Rubella−Specific immune response outcomes - Lin Wang; Iana H. Haralambieva; Inna G. Ovsyannikova; Diane E. Grill; Nathaniel D. Warner; Gregory A. Poland; Richard B. Kennedy (Heliyon, 2023)
The measles-mumps-rubella (MMR) vaccine has been widely used in the US, but measles and mumps outbreaks remain a public health issue in the US and elsewhere, even among individuals immunized with 2 doses of the vaccine. Immune correlates of vaccine-elicited protection against disease are typically assessed with serum antibody assays, but in some cases, these correlates fail to predict immunity, with the complexity and heterogeneity of the immune response. We used multicolor flow cytometry to evaluate changes in the frequency of peripheral T and B cell subsets in 82 study participants after receipt of a third dose of the M-M-RII vaccine (Merck & Co, Inc). We assessed correlations between flow cytometry variables and measles virus (MV), mumps virus (MuV), or rubella virus (RV)−specific immune response outcomes. Following a third vaccine dose, major changes were observed in the T-cell compartment. CD4+ T cell subsets were significantly increased from baseline to day 28, whereas CD8+ T cell subsets were predominantly decreased. Changes in regulatory T cells (Tregs) correlated with RV- and MV-specific immune outcomes and with high- and low−RV antibody responder groups, implicating the importance of Tregs in regulating MMR vaccine−induced immune responses. This information may help define additional correlates of protection and aid in the design of improved vaccines.